Safety and efficacy of Belfeed B MP/ML (endo‐1, 4‐β‐xylanase) as a feed additive for sows, in order to have benefits in piglets, and for all porcine species. (8th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Belfeed B MP/ML as a feed additive for sows in order to have benefits in piglets and for all porcine species. This additive contains endo‐1, 4‐β‐xylanase produced by a genetically modified strain of Bacillus subtilis and it is authorised in the European Union as a feed additive for poultry for fattening, weaned piglets and pigs for fattening. The applicant requested the extension of use of the additive to sows in order to have benefits in piglets and to all porcine species at any developmental stage at 10 IU/kg feed. The FEEDAP Panel concluded that there are no concerns for consumer safety and no risks for the environment are expected from the use of Belfeed B MP/ML in all Suidae species. The additive is not irritant for skin or eye but it should be considered a potential respiratory sensitiser for the users, the Panel could not conclude on the potential of the additive as a potential dermal sensitiser. Considering the results from a tolerance trial done in weaned piglets, those in a subchronic oral toxicity study and the nature/origin of the product under assessment the Panel concluded that the additive is safe for all porcine species at any developmental stage. The data previously assessed in piglets and pigs for fattening allowed to conclude that the additive is efficacious at 10 IU/kg feed in suckling piglets and all Suidae species from suckling to slaughter. The data submitted to support the efficacy for sows was considered insufficient and therefore the Panel could not conclude on the efficacy in sows.